Designing Learning Sequence Metalic Bonding Concept Through Model of Educational Reconstruction Framework - Euis Nursa'adah; Liliasari Liliasari; Ahmad Mudzakir (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
The problem in this research is that students are more familiar with the application of metallic bonding than its concept. This is because the characteristics of the concept are abstract concepts with real context. It makes students more interested in studying the phenomenon but lack to explain the concept and some students show misconception. Therefore this research aims to design learning sequences of metallic bonding topics using the framework model of educational reconstruction (MER). This sequence considers the students’ and scientists’ conception. Considering the initial conception of students in designing learning sequences provides benefits for students. Through MER, learning sequences begin by analyzing student conceptions through semi-structured interviews and concept maps designed by students. Scientific conception analysis is done through concept analysis of several text books that are often used in learning. There are three criteria of students’ conception they are prefer to scientist conception, misconception, and incompetence. Based on the three criteria, learning sequences are produced with the aim to bringing students' conceptions toward scientific conceptions.